THE PYTHAGOREAN THEOREM: ANCIENT ROOTS AND MODERN SIGNIFICANCE - Mirzakimova Dilnavoz Rashid qizi (PEDAGOGS, 2025)
Abstract: This article explores the historical origins and development of the Pythagorean Theorem, its early conceptions, and Pythagoras’s contribution to this theorem. It also discusses the theorem’s importance in mathematics and beyond, its applications, and its role in modern education.